Students' Perspectives: BTS Role in Stimulating English Language Learning - Dinda Rachmadanti Nurhaliza; Aswir Aswir (English Language in Focus (ELIF), 2023)
This research was focused to analyze the students’ responses towards BTS’s influence in stimulating English language learning motivation. This is viewed from the students – who are BTS fans (ARMY) perspective. Based on the analysis, the students’ perspectives are characterized into 3 perspectives, they are behaviorist, cognitivist, and constructivist. In this research, the student’s perspective shows that these 3 learning perspectives are engaged in their learning process through the role of BTS as their stimulation and media for English learning. The data findings also prove that BTS has become an influential factor that attracted students to learn English and pushes their motivation to practice it. The analysis signified that students like learning English better when they are encouraged, interested, and have an access to this media. It means BTS facilitates their understanding of the skills they are acquiring. As a result, their skills are developed and improved well. Moreover, students can use their English language skills to help them achieve their initial goal of studying it. Therefore, It is noteworthy that students’ participation in the study acknowledges the crucial role of BTS as a stimulation of their motivation and asserted the importance of incorporating it in English language learning. As result, BTS does help students to stimulate their English language learning.